EFFECTS OF AMPLITUDES OF EXTERNAL MECHANICAL EXCITATION ON VIBRATION RESPONSE OF PIPING SYSTEM - DZULHIKAM, DZULAISAR (IRC, 2021)
Piping system plays an important role in many industries to transport fluid from one location to another.